Differences in gray matter volume corresponding to delusion and hallucination in patients with schizophrenia compared with patients who have bipolar disorder - Song J (Dove Medical Press, 2015)
Jinuk Song,1 Doug Hyun Han,1 Sun Mi Kim,1 Ji Sun Hong,1 Kyung Joon Min,1 Jae Hoon Cheong,2 Bung Nyun Kim3 1Department of Psychiatry, Chung Ang University Hospital, 2Uimyung Research Institute for Neuroscience, Samyook University, 3Department of Psychiatry, Seoul National Hospital, Seoul, South Korea Background: Although schizophrenia and bipolar disorder (BD) are classified as different disease entities, they share critical pathognomonic symptoms in terms of hallucination and delusion. Because the characteristics of clinical symptoms are not sufficient to differentiate schizophrenia from BD, several studies have applied brain imaging methods to provide biological evidence of differences. We compared gray matter (GM) volume differences in schizophrenia and BD patients and examined volumetric differences associated with hallucination and delusion in these two groups.Methods: Ninety-three schizophrenia patients and 75 BD patients who were followed for at least 3 years in an outpatient department were recruited for this study. Magnetic resonance data from 71 schizophrenia patients and 44 BD patients were obtained using a 3.0 T scanner. Volumetric differences were analyzed using Matlab 8.0.0 and SPM8 software.Results: The results showed that delusion symptoms were negatively correlated with GM volume within both frontal and both temporal cortices in the schizophrenia group and were negatively correlated with GM volume within the bilateral frontal cortices in the BD group. Hallucination symptoms were negatively correlated with GM volume within the bilateral frontal, bilateral temporal, and left parietal cortices in the schizophrenia group and were negatively correlated with GM volume within the bilateral frontal, right parietal, occipital, and insular cortices in the BD group.Conclusion: Delusions in schizophrenia were correlated with GM volume in multiple brain regions, including the frontal, temporal, and parietal cortices, compared to those in patients with BD. Hallucination was associated with temporal lobe GM volume in patients with schizophrenia and with insular cortex GM volume in patients with BD. Keywords: schizophrenia, bipolar disorder, delusion, hallucination, voxel-based morphometry